Karya Seni â€œWayang Orang Rahwana Wirodhaâ€: Kualitas Kepenarian pada Sosok Rahwana - Samsuri Samsuri (Greget, 2009)
As we know, dance have a strong energy just for who capable to deepen and exploit the strength inside with the media moving and body. Existing ability in every motion, able to build up a strong individual appearance. Javanese dance has own typical movement. This matter relied on body possibilities formed by tradition, in interaction and dialoguing with the situation outside. With the properties of manner of expression and its essence value, tradition appropriately able to give the possibilities to be entered, to be explored, to create of new tradition among growth various artistic form of dance performance. Many styles and approaches, in the end become the way of how to mean dance from different side where exploration use body can attend to fluctuate according to its context. This work try to elaborated spirit of exploration to get knowing deeper about the character or Rahwana, subject presentation of gagahan in Javanese dance. Keyword : Rahwana, gagahan, character